2021
DOI: 10.1177/0271678x211039598
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-relevant microbiome signature of the stroke brain, gut, spleen, and thymus and the impact of exercise

Abstract: Stroke remains a significant unmet need in the clinic with few therapeutic options. We, and others, have implicated the role of inflammatory microbiota in stroke secondary cell death. Elucidating this inflammation microbiome as a biomarker may improve stroke diagnosis and treatment. Here, adult Sprague-Dawley rats performed 30 minutes of exercise on a motorized treadmill for 3 consecutive days prior to transient middle cerebral artery occlusion (MCAO). Stroke animals that underwent exercise showed 1) robust be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…The key role of the peripheral immune system in the pathological symptoms of stroke supports the notion that sequestration of deleterious brain immune responses may benefit from regulation of the systemic immune signaling pathways representing novel therapeutic targets for stroke [ 65 , 66 ]. Recent studies show that targeting regenerative medicine-based therapies to peripheral organs, such as the spleen and the gut, reduces behavioral and histological deficits associated with experimental stroke [ 67 , 68 ]. Accumulating evidence also indicates that MHC molecules may attenuate stroke-induced neuroinflammation by tapering harmful immune and inflammatory alterations in the periphery [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key role of the peripheral immune system in the pathological symptoms of stroke supports the notion that sequestration of deleterious brain immune responses may benefit from regulation of the systemic immune signaling pathways representing novel therapeutic targets for stroke [ 65 , 66 ]. Recent studies show that targeting regenerative medicine-based therapies to peripheral organs, such as the spleen and the gut, reduces behavioral and histological deficits associated with experimental stroke [ 67 , 68 ]. Accumulating evidence also indicates that MHC molecules may attenuate stroke-induced neuroinflammation by tapering harmful immune and inflammatory alterations in the periphery [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that targeting regenerative medicine-based therapies to peripheral organs, such as the spleen and the gut, reduces behavioral and histological deficits associated with experimental stroke [ 67 , 68 ]. Accumulating evidence also indicates that MHC molecules may attenuate stroke-induced neuroinflammation by tapering harmful immune and inflammatory alterations in the periphery [ 67 , 68 ]. Thus, recognizing that stroke entails both central and peripheral alterations in the immune response warrants greater understanding of systemic immune signaling pathways to fully explore the pathology and treatment of stroke [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise and physical therapy are critical strategies known to facilitate endogenous and exogenous stem cells in inducing an anti-inflammatory response, which thus offer potential benefits alongside concomitant stem cell therapy for PD [ 123 , 124 , 125 , 126 , 127 , 128 ].…”
Section: Lifestyle Factors Facilitating the Stem Cell Responsementioning
confidence: 99%
“…Valles‐Colomer 16 concluded that Dialister and Coprococcus are positively related to the quality of life and depleted in treatment‐free depression, indicating the potential role of gut microbiota in depression progress. Alterations in gut microbiota are involved in pro‐inflammatory cytokine production and cell death in neurons 17 . Thus, targeting gut microbiota will be instrumental in the improvement of neuroinflammation‐associated CNS disorder 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in gut microbiota are involved in pro‐inflammatory cytokine production and cell death in neurons. 17 Thus, targeting gut microbiota will be instrumental in the improvement of neuroinflammation‐associated CNS disorder. 18 In neuroinflammation conditions, exposure to microbiota induces inflammasome complex to be enriched in cells in CNS when cells activate and then trigger the release of pro‐inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%